Review of studies on Corporate Annual Reports during 1990-2012 - Mobasher, Atefeh; Mohamad Ali, Afida; Abdullah, Faiz Sathi; Chan, Mei Yuit (Australian International Academic Centre, 2013)
Corporate Annual Reports (CARs) are corporate communication tools which have been around for 75 years. They report company’s progress, profits and losses. At first, reports were provided in English, because they were published in an English speaking context. After a while, non-English speaking companies started to publish CARs in English to attract international investments. So far studies on CARs considered themes in text and images of CARs, subgenres of CARs, rhetorical construction, discourse and genre structure. During the last two decade; however, not many studies have been conducted on CARs from a language perspective. We aim to evaluate those studies and provide insight for further research. Findings of previous studies revealed that CARs consist of various sections functioning as sub-genres that have features of their own. Researchers so far have been interested in management forewords section as it is considered to be the most widely read section of CAR, which are supposed to gain the trust of readers. Other sub-genres studied include: operational and financial performance, corporate history and mission statements. As modern CARs are considered to be multimodal, images that appear in CARs have also been studied.